2020
DOI: 10.22146/jtbb.56862
|View full text |Cite
|
Sign up to set email alerts
|

UV Mutagenesis as a Strategy to Enhance Growth and Lipid Productivity of <i>Chlorella</i> sp. 042

Abstract: Microalgae appeared to be an alternative feedstock for renewable biodiesel production due to their capability to accumulate considerable amounts of lipids. In this study, mutagenesis using UVC light with different periods was applied to Chlorella sp. 042 to produce a microalgae strain with high lipid productivity of 45, 60, and 75 min. The Nile red fluorescence method was conducted to select a Chlorella sp. mutant with high neutral lipid and generated one mutant from every UV mutation period, M45-06, M60-02, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The percentage of lipids produced from the biomass of the wild strain and the mutant strain was analyzed and the amount of lipids extracted from the wild strain was noted as 41.3%, whereas the mutant strains of M30-8, M75-24, and M90-18 produced 68.5%, 56.3%, and48.6% of lipids, respectively, at the exponential phase of the culture. Similarly, to our study Rike Rachmayati et al (2020) [14] also found a gradual increase in the growth of biomass in UV-mutated Chlorella sp., compared to the growth of biomass in the wild strain, and Liu et al ( 2015) [28] have shown high lipid content in UV mutagenized microalgal species compared to the lipid content produced by wild strain. Therefore, UV mutation shows an increase in ACC concentration that enhances lipids.…”
Section: Production Of Biomass and Lipids From Wild And Uv-mutated St...supporting
confidence: 91%
See 3 more Smart Citations
“…The percentage of lipids produced from the biomass of the wild strain and the mutant strain was analyzed and the amount of lipids extracted from the wild strain was noted as 41.3%, whereas the mutant strains of M30-8, M75-24, and M90-18 produced 68.5%, 56.3%, and48.6% of lipids, respectively, at the exponential phase of the culture. Similarly, to our study Rike Rachmayati et al (2020) [14] also found a gradual increase in the growth of biomass in UV-mutated Chlorella sp., compared to the growth of biomass in the wild strain, and Liu et al ( 2015) [28] have shown high lipid content in UV mutagenized microalgal species compared to the lipid content produced by wild strain. Therefore, UV mutation shows an increase in ACC concentration that enhances lipids.…”
Section: Production Of Biomass and Lipids From Wild And Uv-mutated St...supporting
confidence: 91%
“…Similarly, to our study Rike Rachmayati et al (2020) [14] also found a gradual increase in the growth of biomass in UV-mutated Chlorella sp., compared to the growth of biomass in the wild strain, and Liu et al (2015) [28] have shown high lipid content in UV mutagenized microalgal species compared to the lipid content produced by wild strain. Therefore, UV mutation shows an increase in ACC concentration that enhances lipids.…”
Section: Production Of Biomass and Lipids From Wild And Uv-mutated St...supporting
confidence: 91%
See 2 more Smart Citations
“…The capacity to undergo mutation is an inherent property of genetic material, including both the genes themselves and also the chromosomes on which the genes are arranged linearly in a certain order ( Obe et al, 1971 ). Various traditional mutagenic sources, such as chemical mutagens, physical mutagens as UV-rays ( Rachmayati et al, 2020 ), γ-rays ( Hidayati et al, 2021 ), and the N + ion beam (C. Wang et al, 2012 , Wang et al, 2012 ), have been developed and successfully applied to acquire valuable strains.…”
Section: Breeding Techniquesmentioning
confidence: 99%